Dalit assertion in society, literature, and history - Ahmad, Imtiaz 1940-2023.; Upadhyay, Shashi Bhushan; Deshkal Society (Gaya, India). Dalit Resource Centre (New Delhi : Deshkal Publication, 2007)
Papers presented at a national seminar held at Bodh Gaya in 2004 organized by Dalit Resource Centre, Deshkal Society (Gaya, Bihar).
pt. A. Dalits and society -- pt. B. Dalits and literature -- pt. C. Dalits in history -- pt. D. Castes among Indian Muslims.
Includes bibliographical references.
Keywords: Dalits -- India -- Social conditions -- Congresses; Indic literature -- Dalit authors -- History and criticism -- Congresses; Dalits in literature -- Congresses; Dalits -- India -- History -- Congresses